MAKROZOOBENTOS YANG BERASOSIASI DENGAN PADANG LAMUN DIPERAIRAN PULAU BARRANG LOMPO, MAKASSAR, SULAWESI SELATAN - Litaay, Magdalena; Priosambodo, Dody; Asmus, Harald; Saleh, Amrullah (Research Center for Biology-Indonesian Institute of Sciences, 2007)
A study on community structure of macrozoobenthos was conducted in the vicinity of seagrass beds Barrang Lompo Island Waters,Makassar. The aim of this study was to investigate species composition, density of macrozoobenthos in the area.Total of 27 species macrozoobenthos were identified during this study.Modiolus micropterus is the most dominant species with density of 542 individu/m .The highest diversity index was found in southeast side (2.38) while northeast side has diversity index only 0.70. Macrozoobentos composition in both station were different with similarity index of 21%.